2017
DOI: 10.3332/ecancer.2017.767
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ERCC1, Bcl-2, Lin28a, and Ki-67 as biomarkers of response to first-line platinum-based chemotherapy in patients with high-grade extrapulmonary neuroendocrine carcinomas or small cell lung cancer

Abstract: BackgroundSmall cell lung cancer (SCLC) and high-grade extrapulmonary neuroendocrine carcinomas (EPNEC) share similar histopathological features and treatment, but outcomes may differ. We evaluated in our study the expression of biomarkers associated with response rate (RR) to chemotherapy and overall survival (OS) for these entities.Materials and MethodsThis is a multicentre retrospective analysis of advanced EPNEC and SCLC patients treated with platinum-based chemotherapy. Paraffin-embedded tumour samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Ki-67 expression was low in the immunohistochemical and gene expression results as well. This coincides with the results reported by de M Rêgo et al [ 27 ] showing the antiproliferative role of CPT-11 that could explain the tongue's mucosal damage detected in this study. In the same context, a remarkable thickening of the keratin layer was observed, which was previously explained by the high sensitivity of taste buds to chemotherapy, taste bud damage, and the loss of sensory innervation which has been documented to have a role in disturbed keratinization and a loss of taste sensation [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…Ki-67 expression was low in the immunohistochemical and gene expression results as well. This coincides with the results reported by de M Rêgo et al [ 27 ] showing the antiproliferative role of CPT-11 that could explain the tongue's mucosal damage detected in this study. In the same context, a remarkable thickening of the keratin layer was observed, which was previously explained by the high sensitivity of taste buds to chemotherapy, taste bud damage, and the loss of sensory innervation which has been documented to have a role in disturbed keratinization and a loss of taste sensation [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…Ki-67 labeling index is recommended by the European Society of Neuroendocrine Tumors (ENETS) in the diagnostic evaluation/work-up guidelines of lung NETs 60 . There does not appear to be a meaningful role for the Ki-67 proliferative status in lung NECs to stratify patients for radiotherapy 62 , non-conventional chemotherapy in small tumor series 63 or first-line platinum-based chemotherapy for SCLC 64 .…”
Section: The Role Of Ki-67 Staining In Lung Neuroendocrine Neoplasmsmentioning
confidence: 99%
“…http://bmjopen.bmj.com/ BMJ Open: first published as 10.1136/bmjopen-2020-041961 on 3 March 2022. Downloaded fromOpen accessStudy characteristics and quality evaluationSeven papers, published between 2013 and 2018 including 1268 patients (693 TC, 281 AC, 94 LCNEC and 190 SCLC), fulfilled the inclusion criteria for metaanalysis [18][19][20][21][22][23][24]. All included studies were retrospective and observational in nature, with no prospective studies identified.…”
mentioning
confidence: 99%